The Effecr of RCRR (Read, Cover, Remember, Retell) Reading Strategy In Reading Comprehension for Seventh Grade at SMPN 2 Kota Jambi - Lia Septiana; Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
This research was done aimed at investigating the effect of using RCRR reading strategy towards the students’ reading comprehension at the seventh grade of SMPN 2 Jambi City in academic year 2019/2020. This research carried out in a quantitative method and quasi-experimental design. The sampling technique used in this research was simple random technique. The population of this research was the seventh grades students. The sample was two classes which divided into two group assigned as experimental (VII C) and control class (VII D). The experimental class was taught using the RCRR strategy as a treatment, while the control class was not. To collect the data, the researcher conducted pre-test and post-test of both classes. The researcher used t-test to know the effect of RCRR strategy.After conducting the pre-test, and post-test to both classes and giving the treatment to the experimental class, the researcher analysed the data. The mean score of pre-test session in control class was 55,46 while the mean of experimental class was 56,09. This score was increased in the post-test, the mean score of control class was 69,37 while the mean score of experimental class was 76,25. Based on the calculation, the value of t-test observation was higher compared to the value of t-test table, 5,010 > 1,998 at the degree of freedom (df 32-1=31) and the level of significance 5% in which thealternative hypothesis was accepted. The researcher interpreted the result that the RCRR strategy had a significant effect toward the students’ reading comprehension of seventh grade at SMPN 2 Jambi City. Key Words: Read, Cover, Remember, Retell.